Multimedia multicast wireless communications with phase-shift-key modulation and convolutional coding. - Pursley, M.B.
Broadcast or multicast signaling can be employed in a wireless communication network to transmit a message to multiple neighbors simultaneously. The capabilities of the intended recipients may vary in the sense that the communication links to some neighbors may have less interference or attenuation than the links to others. We have previously proposed the use of nonuniform phase-shift key (PSK) signal constellations to allow a transmitter to deliver a basic message to each of the intended receivers and an additional message to the more-capable receivers. In this paper, convolutional coding and nonuniform PSK modulation are combined to provide greater efficiency and increased flexibility. The primary goal of multicast transmission, which is for each designated neighbor to have an acceptable probability of receiving the multicast message correctly, is achieved in a way that permits inclusion of multimedia messages for the more-capable receivers. Performance results and tradeoffs are presented for hard- and soft-decision decoding of convolutionally encoded coherent M-ary PSK multicast transmissions. Our results show that convolutional coding can be used with nonuniform PSK modulation to transmit additional information in mobile communication systems with little degradation to the basic information
Keywords: M-ary PSK; Broadcast signaling; Convolutional coding; Hard-decision decoding; Mobile communication systems; Multicast message; Multicast signaling; Multimedia multicast wireless communications; Nonuniform PSK modulation; Phase-shift key; Phase-shift-key modulation; Soft-decision decoding